The Effects of Collaborative Activities onYoung Children’s Attitudes toward People with Disabilities by Using FairyTales on Disability Awareness - Cho, So Hee; Park, Mi Hwa (Korean Journal of Physical, Multiple and Health Disabilities, 2023)
Purpose The purpose of this study was to investigate the effects of collaborative activities on young children’s disability acceptance attitudes by using fairy tales on disability awareness. Method The study was conducted on 66 children who are four years old and enrolled in a general kindergarten in S-si, Gyeonggi-do. Experimental group A, composed of 22 students, was instructed to only listen to the fairy tales on disability awareness; experimental group B, composed of other 22 students, was to listen the same fairy tales and participate in collaborative activities using the fairy tales; and lastly, a control group of 22 students, the rest of the participants, was to participate in the daily education program at the kindergarten. The experimental treatment was conducted twice a week for six weeks for a total of 12 sessions. Results First, the children in the experimental group A showed higher disability acceptance attitudes than those in the control group C. Second, the children in the experimental group B showed higher disability acceptance attitudes than those in the experimental group A. Conclusion The method of linking to fairy tales and participating in collaborative activities can be a meaningful teaching-learning technique to improve the disability acceptance attitudes of children without disabilities.
Keywords: collaborative activity; disability acceptance attitude; fairy tale on disability awareness